Pengaruh Profitabilitas dan Leverage Terhadap Agresivitas Pajak dengan Kepemilikan Institusional Sebagai Variabel Moderasi - Prasetya, Gresia Mahatma Widyadana; Hariyono, Anwar (Universitas Muhammadiyah Gresik, 2023)
This study aims to examine the effect of profitability and leverage on tax aggressiveness with institutional ownership as a moderating variable in consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The population used is manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange (IDX) in 2018-2020. By using purposive sampling, the final sample is 35 companies. The amount of data obtained is 35 x 3 years = 105 observational data, there are 6 data identified as outlier data, the number of final samples obtained is 99 companies. Hypothesis testing in this study using descriptive analysis method with the analysis tool Moderating Regression Analysis (MRA) with the help of the SPSS application. The independent variables used in this study are profitability and leverage, tax aggressiveness as the dependent variable and institutional ownership as a moderating variable. Based on the research results, it is known that profitability and leverage has no effect on on tax aggressiveness and institutional ownership is able to moderate the effect of profitability on tax aggressiveness and profitability is not able to moderate the effect of leverage on tax aggressiveness.